3D Printed Bioreactor Enabling the Pulsatile Culture of Native and Angioplastied Large Arteries - Matos, Rolando S.; Maselli, Davide; McVey, John H.; Heiss, Christian; Campagnolo, Paola (Frontiers in Cardiovascular Medicine, 2022)
Routine interventions such as balloon angioplasty, result in vascular activation and remodeling, often requiring re-intervention. 2D in vitro models and small animal experiments have enabled the discovery of important mechanisms involved in this process, however the clinical translation is often underwhelming. There is a critical need for an ex vivo model representative of the human vascular physiology and encompassing the complexity of the vascular wall and the physical forces regulating its function. Vascular bioreactors for ex vivo culture of large vessels are viable alternatives, but their custom-made design and insufficient characterization often hinders the reproducibility of the experiments. The objective of the study was to design and validate a novel 3D printed cost-efficient and versatile perfusion system, capable of sustaining the viability and functionality of large porcine arteries for 7 days and enabling early post-injury evaluations. MultiJet Fusion 3D printing was used to engineer the EasyFlow insert, converting a conventional 50 ml centrifuge tube into a mini bioreactor. Porcine carotid arteries either left untreated or injured with an angioplasty balloon, were cultured under pulsatile flow for up to 7 days. Pressure, heart rate, medium viscosity and shear conditions were adjusted to resemble arterial in vivo hemodynamics. Tissue viability, cell activation and matrix remodeling were analyzed by immunohistochemistry, and vascular function was monitored by duplex ultrasound. Culture conditions in the EasyFlow bioreactor preserved endothelial coverage and smooth muscle organization and extracellular matrix structure in the vessel wall, as compared to static culture. Injured arteries presented hallmarks of early remodeling, such as intimal denudation, smooth muscle cell disarray and media/adventitia activation in flow culture. Duplex ultrasound confirmed continuous pulsatile blood flow conditions, dose-dependent vasodilator response to nitroglycerin in untreated vessels and impaired dilator response in angioplastied vessels. The scope of this work is to validate a low-cost, robust and reproducible system to explore the culture of native and injured large arteries under pulsatile flow. While the study of vascular pathology is beyond the scope of the present paper, our system enables future investigations and provides a platform to test novel therapies and devices ex vivo, in a patient relevant system.